The effect of a proposed unit in science based on PISA standards in developing life problem-solving skills among Prep school students - Alkest, Naglaa Fauzy Esmaeil; Taha, Mahmoud Ebrahim; Ghalwash, Mohamed Mostafa (Journal of Curriculum and Teaching Methodology, 2024)
The current study aimed to identify life problem-solving skills that could be cultivated among middle school students, and to develop these skills through the implementation of a proposed unit within the science curriculum, aligning with the standards set forth by the Program for International Student Assessment (PISA). The study sample comprised 49 male and female students in the second preparatory grade at Batita Preparatory Mixed School in Kafr El-Sheikh. Tools employed included a life problem-solving skills test. The researcher utilized both descriptive analytical and experimental approaches, employing a quasi-experimental design. The findings of the study yielded a list of four key life problem-solving skills: exploration and understanding, representation and formulation, planning and implementation, and observation and reflection. Additionally, a statistically significant difference was observed between the average scores in the pre- and post-measurements of the research tool, with higher scores favoring the post-measurement. The study recommends the necessity of enhancing science curricula during the preparatory stage, aligning with the standards outlined by the International Program for Assessment (PISA), and emphasizing the development of requisite knowledge, skills, competencies, and attitudes among preparatory stage students.